(Ferrocenylpyrazolyl)zinc(II) benzoates as catalysts for the ring opening polymerization of ε-caprolactone. (18th April 2015) - Obuah, Collins; Lochee, Yemanlall; Jordaan, Johan H.L.; Otto, Daniel P.; Nyokong, Tebello; Darkwa, James
Graphical abstract: Eight ferrocenylpyrazolylzinc benzoates that act as catalysts, instead of initiators, for the ring opening polymerization of ɛ-caprolactone to produce polycaprolactones. Abstract: The reaction of Zn(OAc)2 and C6 H5 COOH or 3, 5-NO2 -C6 H3 COOH with 3-ferrocenylpyrazolyl-methylenepyridine (L1 ), 3-ferrocenyl-5-methylpyrazolyl-methylenepyridine (L2 ), 3-ferrocenylpyrazolyl-ethylamine (L3 ) and 3-ferrocenyl-5-pyrazolyl-ethylamine (L4 ) afford the corresponding complexes [Zn(C6 H5 COO)2 (L1 )] (1 ), [Zn(C6 H5 COO)2 (L2 )] (2 ), [Zn(3, 5-NO2 -C6 H3 COO)2 (L1 )] (3 ), [Zn(3, 5-NO2 -C6 H3 COO)2 (L2 )] (4 ), [Zn(C6 H5 COO)2 (L3 )] (5 ), [Zn(C6 H5 COO)2 (L4 )] (6 ), [Zn(3, 5-NO2 -C6 H3 COO)2 (L3 )] (7 ) and [Zn(3, 5-NO2 -C6 H3 COO)2 (L4 )] (8 ). These complexes behave as catalysts for the ring opening polymerization of ɛ-caprolactone to produce polymers with molecular weight that range from 1480 to 7080 g mol −1 and exhibited moderate to broad PDIs. Evidence of these complexes acting as catalysts was obtained from both the polymerization data and kinetic studies. The polymerization data show that variation of the [CL]/[C] from 100 to 800 produced PCL with relatively the same molecular weight indicative of a catalyst behavior. The appearance of induction period in kinetic plots strengthens the fact that these complexes are catalysts rather than initiators. MALDI-TOF MS and 1 H NMR data show di-hydroxy end groups, which support the coordination mechanism rather than insertion mechanism. To understand the broad PDIs obtained for some of the polymer, the electronic properties of the zinc complexes were investigated using cyclic voltammetry. The results show that the zinc complexes containing amine based ligands are highly electrophilic therefore making them unstable, hence the broad PDIs observed for zinc complexes containing amine based ligands. Among the eight complexes investigated, complex7 is the most active catalyst with k p value of 1.18 × 10 −7 h −1 mol −1 at 110 °C.